Al-Maslahat and Development of Islamic Law - SA, Romli; Zuraidah, Zuraidah (Universitas Islam Negeri Raden Fatah Palembang, 2023)
The Topic of this article/research is “Al-Maslahat And Development of Islamic Law”. There are three main problems which is attractive to elaborate in this article, namely; First, How are the essence and existence of al-Maslahat? Second, How is the al-Maslahat become a basic for development of Islamic law? And the third, How is the function and position of al-Maslahat for Islamic law product? Talking about Al-Maslahat is one object and very attractive in study of Islamic law theory. And it is important part that related with the Maqashid al-Syari’ah. The method that used in this writing/research is “The al-Tasyri’-methode by using “Istishlahiy approach”. Many of Muslims Scholars or the Experts of Regulation of Islamic jurisprudence-wheather at classic era or nowadays—are talking about the existence and position al-Maslahat in Islamic law regulation by using Istishlahiy approach. According to the experts of Islamic Jurisprudence, al-Maslahat can be used as the cause or ratio legis (al-‘Illat) in determining Islamic law regulation. And sometimes, al-Maslahat often called by al-Istidlal, namely logic argumentation or logical reasoning. Through this article/research, we found that al-Maslahat, beside it is functioned as part of method In Islamic law theory but it is also used to develop Islamic law it self. And al-Maslahat is used very widest in determining and development of Islamic law, especially concerning with the contemporary issues. So Imam Malik ever said that where ever you get advantageous and it is not contrary with the content of al-Quran wa al—Sunnah, that is al-Syari’ah (Islamic law).